Exploring Lecturers' Proficiency in Argumentative Writing: Rhetorical Strategies, Coherence, and Linguistic Challenges - Marnita, Rina; Zulprianto, Zulprianto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This study examines lecturers' competence in argumentative writing, emphasizing the rhetorical tactics, coherence, and linguistic difficulties encountered during the process. This research seeks to uncover the strengths and opportunities for growth in academic writing among lecturers, given its crucial role in higher education. The study used a qualitative methodology to investigate a sample of argumentative essays authored by lecturers from diverse fields, assessing the efficacy of their rhetorical methods in articulating and substantiating arguments. The research further examines the coherence of their work, assessing the logical structure and connectivity of ideas and arguments. The research also examines prevalent linguistic obstacles, including clarity, syntax, and vocabulary concerns, that affect the overall quality of argumentative writing. The results indicate that although instructors have robust subject expertise, deficiencies in language competency and argumentative techniques frequently impede the clarity and effectiveness of their work. This study elucidates the necessity for professional development programs designed to improve instructors' academic writing skills, specifically in formulating coherent and rhetorically successful arguments.